The effect of communication in identity in virtual project managements - Eftekhari, Fathollah; Haron, Nuzul Azam (Bret Research Publication Group, 2014)
One of the significant issues confronting the virtual project management teamsis supposed to be the corporate identity. The corporate identity of members ofvirtual teams is overwhelmed due to the lack of counter Communications. Inthe present article, it is attempted to survey the effects of Communications onthe corporate identity and analyze its corporate results on the members ofteam.Results achieved through structural equations modeling test indicate thatthere is a very strong causal relationship between the corporate identity andcorporate conducts such as satisfaction, commitment and involvement with theand OCB as a result of communications.